Social determinants in the delay of starting colorectal cancer treatment - Amanda Almeida Gomes Dantas; Nayara Priscila Dantas de Oliveira; Luís Felipe Leite Martins; Marianna de Camargo Cancela; Junior Smith Torres-Roman; Dyego Leandro Bezerra de Souza (PLoS ONE, 2026)
Delayed access to colorectal cancer (CRC) treatment leads to disease progression, advanced stages at diagnosis, and reduced survival. In Brazil, Law 12.732/2012 mandates treatment initiation within 60 days of diagnosis; however, disparities persist . To assess compliance with the 60-day treatment initiation window for CRC in Brazil and its association with individual, socioeconomic, and healthcare system factors. We conducted a longitudinal observational retrospective cohort study using data from 65,582 CRC cases diagnosed between 2013 and 2019 in Brazil. Individual-level data were obtained from the Integrator of Hospital Cancer Registries, while socioeconomic and healthcare infrastructure data were extracted from national databases. A Multilevel Poisson Regression model with a random intercept was applied. Approximately forty-two percent of patients experienced treatment delays beyond 60 days, with significant variability among Federal Units (UFs). The highest delay rates were observed in Goiás (60.7%), Pará (60.6%), and Acre (58.4%). Factors associated with delayed treatment included younger age, non-white race, low educational level, rectal tumor location, referral through the Unified Health System (SUS), and receiving treatment outside the patient’s municipality of residence. Social determinants significantly impact CRC treatment delays in Brazil, highlighting the need to strengthen healthcare policies to ensure equitable and timely access to cancer treatment, ultimately improving patient survival.